2001
DOI: 10.1017/s0952523801185093
|View full text |Cite
|
Sign up to set email alerts
|

Tetrachromatic input to turtle horizontal cells

Abstract: Recent physiological experiments support behavioral and morphological evidence for a fourth type of cone in the turtle retina, maximally sensitive in the ultraviolet (UV). This cone type has not yet been included in the models proposed for connectivity between cones and horizontal cells. In this study, we examined the inputs of UV, S, M, and L cones to horizontal cells. We used the high-resolution Dynamic Constant Response Method to measure the spectral sensitivity of horizontal cells without background light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 29 publications
0
25
0
1
Order By: Relevance
“…ERG recordings identify UV cone contributions in zebrafish (Bilotta et al 2005;Hughes et al 1998;Nelson and Singla 2009) and juvenile goldfish (Chen and Stark 1994). Horizontal cell hyperpolarizations to UV light have been reported in turtle (Ammermuller et al 1998;Ventura et al 1999;Zana et al 2001) and fish (Hashimoto et al 1988). Tetraphasic light responses were first described in the 1980s in fish (Fukurotani and Hashimoto 1984;Harosi and Fukurotani 1986;Hashimoto et al 1988); however, with the exception of Japanese dace (Hashimoto et al 1988), we found no reports describing UVpreferring triphasic responses in horizontal cells in any of the above species.…”
Section: Uv Light Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…ERG recordings identify UV cone contributions in zebrafish (Bilotta et al 2005;Hughes et al 1998;Nelson and Singla 2009) and juvenile goldfish (Chen and Stark 1994). Horizontal cell hyperpolarizations to UV light have been reported in turtle (Ammermuller et al 1998;Ventura et al 1999;Zana et al 2001) and fish (Hashimoto et al 1988). Tetraphasic light responses were first described in the 1980s in fish (Fukurotani and Hashimoto 1984;Harosi and Fukurotani 1986;Hashimoto et al 1988); however, with the exception of Japanese dace (Hashimoto et al 1988), we found no reports describing UVpreferring triphasic responses in horizontal cells in any of the above species.…”
Section: Uv Light Responsesmentioning
confidence: 99%
“…In turtle, all horizontal cells are hyperpolarized by UV light stimulation (Ammermuller et al 1998;Ventura et al 1999), but only the triphasic cells receive direct UV cone excitation Zana et al 2001). In fish, triphasic horizontal cells also receive inputs from UV cones (Hashimoto et al 1988), and, in some species of cyprinids, a tetraphasic response-hyperpolarized to red, depolarized to green, hyperpolarized to blue, depolarized to UV-has been reported (De Aguiar et al 2006;Fukurotani and Hashimoto 1984;Harosi and Fukurotani 1986;Hashimoto et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, other extant reptile lineages either lack retinal oil droplets entirely (crocodiles, snakes) or have coloured oil droplets varying from clear to yellow and green, but not red (many lizards) [14]. Like birds, turtles have excellent tetrachromatic colour vision [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most Chelonians exhibit good vision, based on a complex type of eye, which allow them to see and clearly distinguish images and to perceive colours (Granda & Stirling 1965;Ammermüller et al 1995;Twig & Perlman 2004;Mathger et al 2007). Recent physiological experiments have shown that Trachemys dorbignii possess a fourth type of cone in the retina, which is maximally sensitive to the ultraviolet spectrum (Ventura et al 1999;Zana et al 2001).…”
Section: Introductionmentioning
confidence: 99%